Access to medicines and hepatitis C in Africa: can tiered pricing and voluntary licencing assure universal access, health equity and fairness? - Yibeltal Assefa; Peter S. Hill; Anar Ulikpan; Owain D. Williams (BMC, 2017)
Abstract Background The recent introduction of Direct Acting Antivirals (DAAs) for treating Hepatitis C Virus (HCV) can significantly assist in the world reaching the international target of elimination by 2030. Yet, the challenge facing many individuals and countries today lies with their ability to access these treatments due to their relatively high prices. Gilead Sciences applies differential pricing and licensing strategies arguing that this provides fairer and more equitable access to these life-saving medicines. This paper analyses the implications of Gilead's tiered pricing and voluntary licencing strategy for access to the DAAs. Methods We examined seven countries in Africa (Egypt, Ethiopia, Nigeria, Democratic Republic of Congo, Cameroon, Rwanda and South Africa) to assess their financial capacity to provide DAAs for the treatment of HCV under present voluntary licensing and tiered-pricing arrangements. These countries have been selected to explore the experience of countries with a range of different burdens of HCV and shared eligibility for supply by licensed generic producers or from discounted Gilead prices. Results The cost of 12-weeks of generic DAA varies from $684 per patient treated in Egypt to $750 per patient treated in other countries. These countries can also procure the same DAA for 12-weeks of treatment from the originator, Gilead, at a cost of $1200 per patient. The current prices of DAAs (both from generic and originator manufacturers) are much more than the median annual income per capita and the annual health budget of most of these countries. If governments alone were to bear the costs of universal treatment coverage, then the required additional health expenditure from present rates would range from a 4% increase in South Africa to a staggering 403% in Cameroon. Conclusion The current arrangements for increasing access to DAAs, towards elimination of HCV, are facing challenges that would require increases in expenditure that are either too burdensome to governments or potentially so to individuals and families. Countries need to implement the flexibilities in the Doha Declaration on Trade Related Intellectual Property Rights agreement, including compulsory licensing and patent opposition. This also requires political commitment, financial will, global solidarity and civil society activism.